Energy Resilience in Telecommunication Networks: A Comprehensive Review of Strategies and Challenges - Ana Cabrera-Tobar; Francesco Grimaccia; Sonia Leva (Energies, 2023)
As telecommunication networks become increasingly critical for societal functioning, ensuring their resilience in the face of energy disruptions is paramount. This review paper comprehensively analyzes strategies and challenges associated with achieving energy resilience in telecommunication networks. It explores various aspects, including policies, energy backup systems, renewable energy integration, and energy management techniques. This paper discusses how these strategies can be implemented to build resilience across three phases: preparedness (referring to the proactive measures taken in advance), response and relief, recovery and reconstruction. Additionally, it discusses the challenges associated with implementing energy resilience measures, taking into account policies, sustainability and environment, and climate change. By synthesizing existing research and identifying research gaps, this review paper aims to provide insights into the state-of-the-art practices and future directions for enhancing energy resilience in telecommunications, enabling robust and uninterrupted communication services.